The Wild West Turns East: Audience, Ritual, and Regeneration in Buffalo Bill’s Boxer Uprising - Haddad, John (American Studies, 2010)
In the summer of 1900, the Western world turned its attention to Peking (Beijing), China, where the expatriate community found itself trapped in the Foreign Legations, under siege from soldiers of the anti-western Boxer movement. In an effort to rescue the Legations, the United States, European nations, and Japan formed an international relief force that marched to Peking, routed the Boxers, and lifted the siege. Mere months later, William Cody assembled a reenactment of this military engagement that served as the spectacular grand finale for the 1901 edition of the Wild West. Along with describing this rare portrayal of the Far East in the Wild West, this article possesses two additional objectives. First, it seeks to understand the reenactment by situating it among several interrelated contexts: the closing of the frontier, the encroachment of modernity on everyday American life, and the intensifying imperial ambitions of the United States. Second, the article shifts away from the performance itself so as to explore the peculiarly raucous behavior of audiences. Employing the theories of cultural anthropologist Victor Turner, the article suggests that Americans may have used the performance as a rite-of-passage ritual, aiding their transition from the rugged past to the modern industrial present.